(untitled) (Global Journal of Medical Research, 2018)
The aim of this study was to determine the relationship between the distal phalanx angle and the radiological condition of the navicular bone and establish a database of reference values for hoof radiographic A retrospective study was measurements in Chilean horses. performed considering radiographic examinations on 146 feet from 92 horses. Linear and angle measurements of the hoof capsule and distal phalanx were obtained and compared statistically. Radiographic condition of the navicular bone was determined and statistically compared with the radiographic hoof values. Additionally, horses were categorized by breed to elucidate differences between breeds.There was a significant negative correlation between the palmar angle and the navicular score. Also, there was a significant negative correlation between the hoof angle and the navicular score. There were significant statistical differences between the distal phalanx angle, weight-bearing surface of the toe and second phalanx length when compared by breed.The information gathered in this study can help to prevent the presentation or the advance of the radiological changes in the navicular bone. A radiographic-guided shoeing should always be considered. Additionally, the present study provides a database of normal values of the hoof capsule in Chilean horses that can be used by veterinarians and farriers as a guideline for routine and orthopedic shoeing.